Evaluation of Patients with Blunt Abdominal Injuries by Ultrasonography and Multidetector Computed Tomography. - Ravi Kiran G; Harshavardhan NS; Anil U Madurwar; Santhosh D (Asian Journal of Medical Radiological Research, 2019)
Background: Blunt abdominal trauma (BAT) usually occurs due to road traffic accidents (RTA), fall from heights or during sports. Prevalence of intraabdominal injury varies widely, ranging from 7.7% to 65%. The aim of study was to evaluate the role of ultrasonography (USG) & multi-detector computed tomography (MDCT) in identifying intra abdominal injury in patients with blunt abdominal trauma and to compare-provide information that could accurately determine choice of management (non-operative vs operative). Subjects and Methods: This study was a prospective study; total 50 patients were included in this study. This study was conducted at Department of Radio-Diagnosis, Chalmeda AnandRao Institute of Medical Sciences, Karimagar. The study period was during from October 2015 to September 2017. USG examinations were performed with a curvilinear and linear probe on GE Voluson S6& Philips Envisor C HD. Results: A total of 38 cases were positive for intra abdominal injury and 12 cases were negative for intra abdominal injury. 30 patients underwent surgery and the remaining cases were managed conservatively. Most of the patients admitted to this hospital were victims of vehicular accidents. Road traffic accidents (RTAs) as accounting for 33 cases (66%) of the blunt abdominal trauma. Conclusion: The present study concluded that MDCT is the superior diagnostic modality in the diagnosis of blunt abdominal trauma. USG can be a valuable initial investigation; however, USG can miss crucial injuries and may lead to inappropriate management in some patients.